Growing up on the Trobriand Islands in Papua New Guinea. Childhood and educational ideologies in Tauwema - Barbara Senft (Culture and Language Use. Studies in Anthropological Linguistics, 2018)
This volume deals with the children's socialization on the Trobriands. After a survey of ethnographic studies on childhood, the book zooms in on indigenous ideas of conception and birth-giving, the children's early development, their integration into playgroups, their games and their education within their `own little community' until they reach the age of seven years. During this time children enjoy much autonomy and independence. Attempts of parental education are confined to a minimum. However, parents use subtle means to raise their children. Educational ideologies are manifest in narratives and in speeches addressed to children. They provide guidelines for their integration into the Trobrianders' "balanced society" which is characterized by cooperation and competition. It does not allow individual accumulation of wealth - surplus property gained has to be redistributed - but it values the fame acquired by individuals in competitive rituals. Fame is not regarded as threatening the balance of their society.